2023
DOI: 10.1021/jacs.3c11712
|View full text |Cite
|
Sign up to set email alerts
|

Racemic Peptides from Amyloid β and Amylin Form Rippled β-Sheets Rather Than Pleated β-Sheets

Amaruka Hazari,
Michael R. Sawaya,
Maria Sajimon
et al.

Abstract: The rippled β-sheet was theorized by Pauling and Corey in 1953 as a structural motif in which mirror image peptide strands assemble into hydrogen-bonded periodic arrays with strictly alternating chirality. Structural characterization of the rippled β-sheet was limited to biophysical methods until 2022 when atomic resolution structures of the motif were first obtained. The crystal structural foundation is restricted to four model tripeptides composed exclusively of aromatic residues. Here, we report five new ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Additionally, it has been reported that aromatic residues Phe, Tyr, and Trp favor the formation of rippled sheets. 62–64 In our case, the investigated TTR(105–115) peptides possess in their sequence 2 Tyr residues and AFM images strongly support the co-assembly of quasi-racemic fibrils. Accordingly, we observed totally different morphologies in enantiopure l - and d -peptide samples (Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Additionally, it has been reported that aromatic residues Phe, Tyr, and Trp favor the formation of rippled sheets. 62–64 In our case, the investigated TTR(105–115) peptides possess in their sequence 2 Tyr residues and AFM images strongly support the co-assembly of quasi-racemic fibrils. Accordingly, we observed totally different morphologies in enantiopure l - and d -peptide samples (Fig.…”
Section: Resultssupporting
confidence: 70%
“…57 Such predictions were confirmed by other groups as well. 58–61 Very recent study performed by A. Hazari et al 62 demonstrates that racemic mixtures of amyloid-like peptide assemblies possess rippled sheets and it is their generic property. Additionally, it has been reported that aromatic residues Phe, Tyr, and Trp favor the formation of rippled sheets.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, these observations in principle could provide evidence for both spontaneous deracemization and enhanced mechanisms for achieving biological homochirality. In another study, the formation of rippled β-sheets from assembling racemic peptide mixtures is demonstrated . The X-ray crystallography study revealed that peptide sequences ( 26 – 29 ) derived from amyloid β and amylin exhibited the formation of antiparallel rippled β-sheets (Figure n–q) from assembling racemic peptide mixtures.…”
Section: D Architectures By Programmable Fabrication Strategiesmentioning
confidence: 92%
“…Copyright 2011 and 2013, respectively, Wiley-VCH. Panels (e, f), (m), and (n–q) were adapted from ref , ref , and ref , respectively. Copyright 2016, 2011, and 2023, respectively, American Chemical Society.…”
Section: D Architectures By Programmable Fabrication Strategiesmentioning
confidence: 99%